Training farmers using participatory video - David, S. (International Institute of Tropical Agriculture, 2009)
Studies were conducted to train farmers in Ghana in increasing cocoa production and improve safety and labour efficiency by showing new techniques and practices using participatory video. The videos focused on cultural methods to control black pod disease, chemical control of mirids and black pod disease, pruning, harvesting, pod breaking, fermentation and drying. Farmers that adopted the video-promoted practices inreased yield by 20-40%, decreased pesticide use by 10-20% and increased household income by 23-55%.